Dynamics of Screen Time and Physical Activity Patterns: A Study Based on Gender and Type of Sport - Nanda Mei sholihah; Dwi Cahyo Kartiko; Mochamad Ridwan (Jurnal Pendidikan Jasmani (JPJ), 2026)
The use of digital devices has become increasingly prevalent among school-aged adolescents, potentially leading to reduced levels of physical activity. This study aimed to analyze the dynamics of screen time among student athletes enrolled in the Pusat Pembinaan dan Pelatihan Atlet Pelajar (PJPAP) Central Java program, viewed from gender and type of sport perspectives. Screen time was defined as the total duration of digital device use within a 24-hour period, including activities related to learning, entertainment, and communication over the past month. This study employed a quantitative approach with a cross-sectional design. The participants consisted of 25 student athletes (13 males and 12 females) who engaged in structured training six days per week. Data were collected using a structured screen time questionnaire and analyzed using the Shapiro–Wilk normality test, independent t-test, and one-way ANOVA. The results indicated that the average daily screen time of male athletes was 3.47 hours, while female athletes averaged 3.05 hours per day. The independent t-test showed a significant difference in screen time based on gender (p = 0.028). Meanwhile, the one-way ANOVA across five sport disciplines revealed no significant differences in screen time (F = 2.413; p = 0.078). These findings suggest that gender influences screen time patterns among student athletes, whereas differences in sport disciplines do not significantly affect the duration of digital device use.